Penerapan Terapi Rebusan Daun Salam sebagai Terapi Alternatif Pengobatan Hipertensi pada Lansia - Ahmad Aklim Nusantara; Muhammad Hafiz Nugraha; Tjitra Marini; Sherly Meilianty; Wilda Nur Jannah; Nor Afni Oktavia (Lembaga Pengembangan Kinerja Dosen, 2026)
Hypertension is a common non-communicable disease among the elderly and a major risk factor for cardiovascular disorders. Management of hypertension involves both pharmacological and non-pharmacological approaches, including the use of herbal remedies such as bay leaves, which contain flavonoids, tannins, and essential oils with potential antihypertensive effects. This community service activity aimed to assess the effectiveness of health education and bay leaf decoction therapy in increasing knowledge among elderly individuals with hypertension in Batik Village RT 01 & 02. A total of 28 participants attended educational sessions that included lectures, discussions, and practical demonstrations on preparing and using bay leaf decoction. Participants were actively engaged, demonstrated understanding of the preparation process, and could explain the benefits and use of bay leaf decoction as a complementary therapy for hypertension. Evaluation through pre-test and post-test revealed a significant increase in knowledge, with average scores rising from 5.6 to 8.9. Notably, 85.7% of participants scored ≥ 8 following the intervention. The findings indicate that combining education with hands-on demonstration of bay leaf decoction effectively enhances elderly individuals’ understanding of non-pharmacological hypertension management. This approach provides practical guidance for integrating herbal therapy into daily life, promoting self-care, and supporting overall cardiovascular health. The study highlights the value of community-based education and simple herbal interventions as adjunct strategies in controlling hypertension among older adults.